Perda e desperdício de alimentos sob uma perspectiva baseada na economia circular - Oliveira, Mariana Martins de (2019)
One third of food produced for human consumption is lost or wasted globally, representing an opportunity to improve global food security and mitigate the environmental impacts of agriculture. In this context the circular economy arises in order to optimize the use of natural resources by providing a new impetus to the idea of preventing and reducing food waste and thus leading to more sustainable development. From this perspective, the main objective of this dissertation was to identify the main food losses and waste (FLW) in the dairy supply chain and to analyze if these losses could be reused according to the Circular Economy (EC) approach. The results of this dissertation are presented in two articles. The first one sought to identify and systematize articles related to food loss and waste with solutions based on the concept of EC, through a systematic literature review using the StArt tool. Among the results it was found that although there is an increase in this field of research, identified from 2016, it is still a little explored area, since only four articles out of the 25 selected directly relate the FLW with the EC. The second article refers to an ECW approach under the EC conception, focusing on the dairy supply chain, where at first the FLW along the chain was quantified from the Mass Balance methodology suggested by “FLW Standard” and secondly reuse and recycling solutions have been proposed from an EC perspective. Among the results found, a FLW of 1.78 kg was identified for each 2.0 kg of cheese produced. The study also demonstrated possible EC applications to reduce FLWs in the Lat Uruguay Dairy supply chain, such as the feasibility of recovering water from whey or generating energy through anaerobic reactors. Finally, among the limitations of this study, it is worth mentioning the few studies carried out with EC proposals that include solutions for FLW in the dairy supply chain and also studies that present economic benefits of the transition from a linear to a circular system in the dairy supply chain dairy products. Overall, the results of this study presented a pioneering attempt to test the methodological principles of the FLW Protocol in the dairy supply chain to obtain satisfactory results. However, for future research, it is suggested to conduct an economic analysis of unmet production potential to obtain monetary values of how much the FLWs represent within Laticínio Alto Uruguay's supply chain.